Development of Unconventional Amide Bond Forming Methodologies - MAGUIRE, AMY (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2020)
A novel methodology for the protection of amines and diamines using 2,2-pyridil, under the influence of N-heterocyclic carbene (NHC) catalysis, has been developed. Extensive experimentation which included the design and synthesis of three generations of benzil substrates was necessary to identify 2,2-pyridil as an excellent amine acylating agent. This methodology is capable of distinguishing between two amines, characterised by small differences in steric bulk. One example which is particularly impressive is the ability of this NHC-catalysed system to distinguish between two secondary amines in a diamine differing by only one carbon unit; i.e. an N-Me substituted amine was exclusively acylated in the presence of an N-Et substituted unit. Alkylation of the nitrogen atom of the subsequent pyridoyl amides derived from the chemoselective acylation of amines by 2,2-pyridil, allowed for amine deprotection. A novel set of conditions were developed which allowed for the deprotection without requiring the harsh acidic and basic hydrolytic conditions associated with cleaving benzoyl units from amines. Hereby, this methodology can be utilised as a highly chemoselective protecting group for amines and amino acids. The development of a new strategy to carry out the aminolysis of tetrachloroisopropoxycarbonyl (TCIC) -substituted azlactones via a phenolic ester intermediate has been carried out. Due to the difficulties associated with controlling the addition of amines to azlactones under catalyst influence, the aminolysis of azlactones under DKR conditions to synthesise orthogonally protected peptides, has so far, to the best of our knowledge, not been achieved. Through use of a substituted phenolate anion, the alcoholysis of azlactones under the control of phase-transfer catalysis (PTC) furnished phenolate esters, which are readily displaced by an amine nucleophile to synthesise orthogonally protected amides and dipeptides. These reactions proceeded with high product yields however, the employment of chiral PTCs failed to invoke high product enantioenrichment. Further experimentation and computational studies are necessary to fully understand this mode of catalysis and may garner further insight into how enantioselectivity in the products may be achieved. However, this novel methodology is, to our knowledge, the first example of racemic azlactones being used to carry out peptide coupling without requiring a S,N-acyl transfer as with NCL or an O,N-acyl transfer as previously reported in the literature to achieve chemical ligation.
APPROVED